BEAD STRINGING TRAINING IN IMPROVING THE FAMILY ECONOMY FOR PKK MOTHERS IN TUMPOK TEUNGOH VILLAGE, LHOKSEUMAWE CITY - Teuku Alfiady; Arinanda; Nazaruddin; Ainol Mardhiah (RADJA PUBLIKA, 2024)
Training on bead stringing was organized as one of the contributions in improving the competence of individuals and community groups, especially mothers in the PKK of Tumpok Teungoh village, Banda Sakti sub-district, Lhokseumawe City. The purpose of the service activity is to provide special knowledge for mothers who have the opportunity to be independent with home-based businesses but do not yet have skills, as well as to establish relationships with fellow local residents. With the implementation of this service, it is hoped that the participants will be able to do the bead stringing business independently and in groups so that they can contribute to meeting family needs. This series of assistance also includes mentoring and training in bead stringing. The training participants consisted of PKK members from Tumpok Teungoh village.